Following "the Roots" of Kratom (Mitragyna speciosa): The Evolution of an Enhancer from a Traditional Use to Increase Work and Productivity in Southeast Asia to a Recreational Psychoactive Drug in Western Countries. (10th November 2015) - Cinosi, Eduardo; Martinotti, Giovanni; Simonato, Pierluigi; Singh, Darshan; Demetrovics, Zsolt; Roman-Urrestarazu, Andres; Bersani, Francesco Saverio; Vicknasingam, Balasingam; Piazzon, Giulia; Li, Jih-Heng; Yu, Wen-Jing; Kapitány-Fövény, Máté; et al.
Abstract : The use of substances to enhance human abilities is a constant and cross-cultural feature in the evolution of humanity. Although much has changed over time, the availability on the Internet, often supported by misleading marketing strategies, has made their use even more likely and risky. This paper will explore the case of Mitragyna speciosa Korth. (kratom), a tropical tree used traditionally to combat fatigue and improve work productivity among farm populations in Southeast Asia, which has recently become popular as novel psychoactive substance in Western countries. Specifically, it (i) reviews the state of the art on kratom pharmacology and identification; (ii) provides a comprehensive overview of kratom use cross-culturally; (iii) explores the subjective experiences of users; (iv) identifies potential risks and side-effects related to its consumption. Finally, it concludes that the use of kratom is not negligible, especially for self-medication, and more clinical, pharmacological, and socioanthropological studies as well as a better international collaboration are needed to tackle this marginally explored phenomenon.